The Emergence in Mining Technology of Digital Gold: Ambiguity Surrounded in the Bitcoin System - Gupta, Abhishek; Das, Biswajit; Bisoyi, Bhubaneswari (International Journal of Engineering and Technology, 2018)
This article is based on the revolutionary development in the year 2008 by Satoshi Nakamoto was of a â€œPeer to peer Electronic cash systemâ€. The purpose of this paper is to analyze research surrounding the anonymity of online transactions using cryptocurrencies and report on the feasibility that does not have a regulatory body. This article takes the wheel around the journey of an unknown secondary invention which emerged as the digital gold across the globe and works as the digital barter system, a stepping stone towards the cashless world. The success wing of the invention was the decentralized mechanism to operate a digital cash system that restricts and checks double payment. Unlike in centralized server system, in the decentralised network, every nod in the network ensures and achieves absolute consensus. Crypto-currencies being unique and volatile are the most talked, researched, observed topic of the past few years. It is no less than an ocean of opportunities which works differently for different set of people. Crypto currencies functionalities and trade revolve around the internet based global markets. The design of the paper follows on from the approach taken by Reid and Harrigan, 2013 in determining whether the transactions made need to be detected and should have an option of rectifying the errors after knowing the peer or the location of the dealer or investor. By doing so, this research tests the interest of the investor and how much an individual will rely on such online mining of currency. Additionally, this will create an atmosphere which can extradite fraudulent or illegitimate transactions.Â Â Â